FAKTOR-FAKTOR DUKUNGAN TERHADAP TINGKAT MOTIVASI UNTUK SEMBUH PADA PENYALAHGUNA NAPZA DI LAPAS KELAS III BATULICIN TAHUN 2024: THE FACTORS OF SUPPORT ON THE LEVEL OF MOTIVATION TO RECOVER IN DRUG ABUSERS AT CLASS III PRISON OF BATULICIN IN 2024 - Juniawan, Herdy; Dewy, Tika Sari; Apriliyanti, Widia (WELL BEING, 2025)
A drug abuser is someone who uses narcotics, psychotropic substances, addictive substances that can threaten health. The high level of drug abuse is due to a lack of internal and external support motivation to recover. The study to determine the factors of support the level motivation to recover in drug abusers. Design study mixed method. The quantitative method was a crosssectional approach and the qualitative method phenomenological approach. The quantitative sample 75 respondents with purposive sampling technique by using a questionnaire, while the qualitative stuy was snowball sampling technique with 6 respondents for interviews. The results of quantitative indicated that independent variables there was correlations, educational factors (p value = 0.045), employment (p value = 0.021), social support (p value = 0.025), family support (p value = 0.033), coping mechanisms (p value = 0.017). Multivariate results indicated that OR 12,987 for the work variable had significant influence on the level motivation to recover. The results qualitative indicated that drug abuse occurred due to relationships and broken homes, and the cause of relapse was due to work. The conclusion of this study factor was work with OR value of 64,89 which had a significant influence on the level motivation to recover.